Testing Latitudinally Dependent Explanations of the Circulation Response to Increased CO2 Using Aquaplanet Models. Issue 18 (27th September 2018) - Shaw, Tiffany A.; Tan, Zhihong
Abstract: The atmospheric circulation exhibits robust responses to increased CO2 that emerge across the climate model hierarchy. Existing theoretical explanations of the circulation response can be grouped according to latitude. Here we test latitudinally dependent explanations of the circulation response to increased CO2 using slab ocean aquaplanet models with latitudinally dependent CO2 concentration. Quadrupling CO2 in the tropics (0–20°) accounts for the strengthening and upward shift of the subtropical jet but does not account for the poleward shift of the Hadley cell edge or extratropical circulation. The tropical response is dominated by regions of descent. When CO2 is quadrupled in high latitudes (60–90°), there is a negligible circulation response. The response to latitudinally dependent increased CO2 is mostly linear and increased CO2 in the midlatitudes (20–60°) dominates. Within the midlatitudes, the subtropics (20–40°) dominate. Thus, story lines explaining the circulation shift in response to increased CO2 should focus on the thermodynamic response in the subtropics. Plain Language Summary: The atmospheric circulation controls the regional response to global warming. There are several robust responses to global warming according to state‐of‐the‐art climate models: (1) the subtropical jet will strengthen and shift upward and (2) the Hadley cell edge, storm tracks, and jet stream will shift poleward. In contrast to the thermodynamic response to climate change, which includes warming of the troposphere, cooling of the stratosphere, warming aloft in the tropics, and Arctic amplification at the surface, robust physically based story lines of the circulation response are lacking. The lack of robust story lines occurs in part because there are many explanations put forward in the literature to explain the circulation response, which have not been properly compared. Here we test latitudinally dependent explanations of the circulation response to increased CO2 using idealized simulations with latitudinally dependent CO2 concentration. The results show that increased CO2 in the tropics accounts for the strengthening and upward shift of the subtropical jet and increased CO2 in midlatitudes accounts for the poleward shift of the Hadley cell edge, storm track, and jet stream. Within the midlatitudes the subtropics dominate. Key Points: We test explanations of the circulation response to increased CO2 using aquaplanet models with latitudinally dependent CO2 concentration Increased CO2 in the tropics accounts for the subtropical jet response The response to increased CO2 is mostly linear, and increased CO2 in the subtropics dominates the circulation shift